The Effect of Motivation on Employee Performance Through Job Satisfaction as an Intervening Variable in the Car Showroom 88 Palembang - Nadilah, Caesa Ayuni; Hildayanti, Siti Komariah; Purnamasari, Endah Dewi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to analyze the effect of motivation on employee performance through job satisfaction as an intervening variable at Mobil 88 Palembang Branch. The data in this study are primary and secondary data collected through questionnaires and interviews. The number of respondents in this study were 35 respondents. The analytical method applied in this study is the analysis of the coefficient of determination. The results of this study prove that motivation has a positive effect on job satisfaction employee performance is also proven to have a positive effect on job satisfaction . The results of this study are expected to be useful for Mobil 88 Palembang Branch to improve employee performance through motivation and job satisfaction